THE RELATION BETWEEN INNOVATION STRATEGY AND COMPANY’S FINANCIAL PERFORMANCE MEDIATED BY INTELLECTUAL CAPITAL AND INTERNAL PROCESS PERFORMANCE - Hariyati Hariyati; Bambang Tjahjadi (Journal of Applied Economics in Developing Countries, 2016)
This research examines the relation between innovation strategy and company’s financial performance through mediation between intellectual capital and internal process performance. The hypothesis in this research is that the innovation strategy affects the financial performance, which is mediated by intellectual capital, and internal process performance. This research is a quantitative research in the explanatory level. The populations of this research are all of the manufacturer companies in East Java. There are 398 companies. The data is collected through questionnaires. There are 135 questionnaires or response rate for 34%. The analysis unit is a business unit. The research respondent is the manager of the business unit in Manufacturing Company in East Java. The research result shows that the intellectual capital and internal process performance mediates partially the relation between innovation strategy and financial performance.Keywords : innovation strategy, mediation, financial performance, intellectual capital, internal process performance